Cigarette Smoking and Risk of Intracranial Aneurysms in Middle-Aged Women. (16th November 2020) - Gomez-Paz, Santiago; Ogilvy, Christopher S; Kicielinski, Kimberly P; Salem, Mohamed M; Akamatsu, Yosuke; Waqas, Muhammad; Rai, Hamid H; Catapano, Joshua; Muram, Sandeep; Elghareeb, Mohammed; Siddiqui, Adnan H; Levy, Elad I; et al.
Abstract: INTRODUCTION: We previously reported a single-center study demonstrating that smoking confers a 6-fold increased risk for having an unruptured intracranial aneurysm (UIA) in women 30–60 years of age and this risk was higher if the patient had chronic hypertension. METHODS: We performed a multicenter case-control study on women between 30–60 years-old, that had a magnetic resonance angiography (MRA) during 2016–2018. Cases were those with an incidental UIA, and these were matched to controls based on age and ethnicity. A multivariable conditional logistic regression was conducted to evaluate smoking status and hypertension differences between cases and controls. RESULTS: From 545 eligible patients, 113 aneurysm patients were matched to 113 controls. The most common reason for imaging was due to chronic headaches in 62.5% of cases and 44.3% of controls. A positive smoking history was encountered in 57.5% of cases and in 37.2% of controls. A multivariable analysis demonstrated a significant association between positive smoking history (OR 3.7 CI 1.61-8.50), hypertension (OR 3.16 CI 1.17-8.52), and both factors combined with a diagnosis of an incidental UIA (OR 6.9 CI 2.49-19.24). CONCLUSION: Women between 30–60 years-old with a positive smoking history have a 4-fold increased risk for having a UIA, and a 7-fold increased risk if they have underlying chronic hypertension. These findings indicate that women between 30–60 years-old with a positive smoking history might benefit from a screening recommendation.